STUDI KEPADATAN JARINGAN KOLAGEN PADA PROSES KESEMBUHAN LUKA IRIS KULIT ANJING ( Canis familiaris) YANG DITERAPI SAMBILOTO (Andrographis paniculata) - , FARICH AZHAR PURNOMO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research was conducted to study the microscopic figures of the collagen density day 3 and 9 on the dog wound that treated with dried sambiloto and fresh scours of sambiloto. The research were involved 4 local dogs, aged between 7-9 months were divided into 3 groups (A, B, and C). Each dog was incised in 3 different spots on the right flank. Group A as the control group, group Bâs incision wound being treated with dried sambiloto, and group Câs incision wound being treated of fresh scours of sambiloto. On the 3rd and 9 th day, tissue samples of wound healing around 2 x 2 cm were biopsied and put into 10% formalin, the samples were sent to the Histology Laboratory Faculty of Veterinary Medicine to make the histology preparations and getting stained with Mallory staining. The microscopic results showed the density of collagen in dogs group B and dogs group C were more dense than the dogs in group A. Statistical analysis using T-test on day 3 comparison between group A dan group B results indicate insignificant(P>0,05), while in group A and group C results showed a significant results (P<0,05), group B and group C also showed significant results (P>0,05). On day 9 th comparison between group A and group B showed significant results (P>0,05), similiarly between group A and group C, group B and C also showed significant results (P>0,05). As the conclusion based on the results and discussion, the collagens density in dogs were treated with sambiloto were higher compared to the control group. Dogs in group C (fresh scours of sambiloto) showed the best results compared to the other groups. Concentration of fresh scours of sambiloto leaf are recommended as a medication for wound.